ELECTRODEPOSITION AND MORPHOLOGY OF COPPER POWDER PARTICLES OBTAINED AT DIFFERENT CURRENT REGIMES - M. G. Pavlović; M. V. Tomić; Lj. Pavlović; V. Maksimović; N. D. Nikolić (Journal of Engineering & Processing Management, 2009)
The effect different deposition regimes (constant and reversing currents), on the powdered copper electrodeposits morphology were investigated. The morphology of electrodeposited copper powder was investigated using a scanning electron microscope (SEM). The effect of the current amplitude, cathodic to anodic time ratio and period of the current wave are discussed. It is shown that the parameters determining the reversing current wave determine the micro-morphology of the copper powder particles deposited.
Keywords: copper; electrolysis; morphology of particles